Study of Some Medicinally Useful Climbers and Creepers at Abheda Biological Park, Kota, Rajasthan - Vijayvargiya, Priyal; Shrivastava, Pratima (Journal for Research in Applied Sciences and Biotechnology, 2023)
The research paper represents the results of first study on diversity of medicinally useful lianas at abheda biological park situated at district Kota –Rajasthan. The study was conducted with the aim to explore lianas (climber, creepers, and vine) species which are directly used for medicinal purposes to prepare a checklist of our medicinally important wild plant resources found at the study area. In this paper total fourteen species belonging from Cucurbitaceae, Vitaceae, Fabaceae, Convolvulaceae, Sapindaceae Manispermaceae, Passifloraceae and Apocynaceae families are mentioned and investigated for their direct uses and a list is prepared. The study was carried out to add on knowledge to wild plant resources and local medicinally useful plants which are generally avoided due to lack of knowledge about their use or most often lack of knowledge about their presence. Labelled images with most of distinctive features are also attached to facilitate the identification of species. Diverse composition of plant species is also showing about the potential of wild resources of study area.